2012
DOI: 10.1124/dmd.112.048496
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Subcutaneous Absorption of Rituximab in Rats

Abstract: Absorption of monoclonal antibodies (mAbs) after s.c. injection results from the interplay among several kinetic processes. The aims of this study were to investigate the absorption mechanisms of rituximab in rats by using slow s.c. infusion and coadministration with nonspecific IgG or hyaluronidase, and to evaluate the predictive performance of the pharmacokinetic model previously developed to describe the nonlinear absorption behavior of mAbs. Rituximab serum concentrations were measured after s.c. coadminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 29 publications
4
43
0
Order By: Relevance
“…This suggested that FcRn plays a role in antibody tissue distribution. Garg et al further proposed that the muscle and skin 8,9 are among the major sites of IgG catabolism, where FcRn-mediated transport from blood to tissue contributes significantly to IgG extravasation in these two tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that FcRn plays a role in antibody tissue distribution. Garg et al further proposed that the muscle and skin 8,9 are among the major sites of IgG catabolism, where FcRn-mediated transport from blood to tissue contributes significantly to IgG extravasation in these two tissues.…”
Section: Introductionmentioning
confidence: 99%
“…A mathematical model has been developed to study absorption mechanisms of mAbs in rats using rituximab as a model drug (12,13). The bioavailability of rituximab following SC administration decreases inversely with the dose level, and this nonlinear behavior is assumed to manifest from saturation of FcRn-mediated protective binding at the absorption site (14).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this hypothesis, FcRndeficient mice were reported to have threefold lower bioavailability of an IgG1 antibody compared to wild-type mice (22). Similarly, increased affinity of mAbs to FcRn at pH 6.0 (akin to lysosomal pH), but not pH 7.4, was associated with greater SC bioavailability in mice (27,28), while coadministration of rituximab with IgG (and thus saturating the FcRn interaction) reduced its bioavailability in mice (29). In contrast, engineering a series of five IgG4 variants for enhanced FcRn interaction failed to consistently improve SC bioavailability in cynomolgus monkeys (30), although a trend was suggested for those associated with lower starting bioavailability.…”
Section: Discussionmentioning
confidence: 90%